The Exergo-Economic and Environmental Evaluation of a Hybrid Solar–Natural Gas Power System in Kirkuk - Ali Alfaris; Abdulrazzak Akroot; Emrah Deniz (Applied Sciences)
The increasing environmental challenges posed by the widespread use of fossil fuels and the fluctuating nature of renewable energy have driven the need for more efficient and sustainable energy solutions. Current research is actively exploring hybrid energy systems as a means to address these issues. One such area of focus is the integration of Organic Rankine Cycles (ORCs) with gas and steam turbines, utilizing both natural gas (NG) and solar parabolic trough collectors (PTCs) as energy sources. This study examines the performance of a hybrid system implemented in Kirkuk, Iraq, a region known for its substantial solar radiation. Previous research has shown that hybrid systems can effectively enhance energy conversion efficiency and reduce environmental impacts, but there is still a need to assess the specific benefits of such systems in different geographical and operational contexts. The analysis reveals a thermal efficiency of 59.32% and an exergy efficiency of 57.28%. The exergoeconomic analysis highlights the optimal energy cost at USD 71.93/MWh when the compressor pressure ratio is set to 8 bar. The environmental assessment demonstrates a significant reduction in <semantics>CO2</semantics>/emissions, with a carbon footprint of 316.3 kg <semantics>CO2</semantics>/MWh at higher compressor pressure ratios. These results suggest that integrating solar energy with natural gas can substantially improve electricity generation while being both cost-effective and environmentally sustainable.